The Mixed-Methods Study of Nursing Perception on Organizational Culture and Turnover in Hospital - Susi Verawaty Sinaga; Emiliana Tarigan; Agustinus Bandur (Indonesian Journal of Health Research, 2019)
Introduction. Organizational culture is a set of values that must be understood by all individuals involved in organization where achievement of a conducive organizational culture depends on many factors. Organizational culture that is not conducive in implementation of the hospital service system, is observed as one of the factors causing nurse turnover which can be detrimental to the hospital. This study aims to explore the thematic relationship of the influence of organizational culture with nurse turnover. Methods. The Mixed-Methods concurrent triangulation study (a balanced mix of quantitative and qualitative) with the independent variables are characteristic of organizational culture, socialization process of organizational culture and the role of managers in organizational culture. The sample in this study were 232 nurse respondents and 15 participants consisting of nurses, head nurse and the head of the installation at a hospital in South Jakarta. Results. Regression test results showed a significant influence between the characteristics of organizational culture (ß=311, p = .000), the role of managers in organizational culture (ß=240, p = .006) while the process of socializing organizational culture obtained significant results but does not have an effect on nurse turnover (ß= 101, p = 210). The results of qualitative analysis found five themes related to the characteristics of organizational culture, four themes about the socializing process of organizational culture, three themes related to the role of managers in organizational culture. Conclusion. It is important for nurse managers to pay attention to the creation of good organizational culture characteristics, the implementation of orientation socialization processes, and the assessment of consistent career paths for all individuals in hospital organizations.